Pengaruh Pengalaman dan Jarak Tempuh Melaut terhadap Pendapatan Nelayan di Kabupaten Cilacap - Kristian Cahyandi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
The study, aims to analyze the effect of fishing experience and distance traveled individually and collectively on fishermen's income in Cilacap Regency. This study also analyzes the most dominant factor between the two variables to increase fishermen's income in Cilacap Regency. The research was conducted using primary and secondary data. Primary data was taken from interviews with fishermen about the experience and distance traveled to sea in Cilacap Regency. This data is supported by other relevant secondary data using Multiple Linear Regression.The results showed that the variables of experience and distance traveled simultaneously affect the income of fishermen in Cilacap Regency. Whereas partially, the experience variable has a significant effect on the income of fishermen in Cilacap Regency, while the variable fishing distance does not have a significant effect on the income of fishermen in Cilacap Regency.